The Disparities in Patient Portal Use Among Patients With Rheumatic and Musculoskeletal Diseases: Retrospective Cross-sectional Study - Enid Y Sun; Carolina Alvarez; Leigh F Callahan; Saira Z Sheikh (JMIR Publications, 2022)
BackgroundDuring the COVID-19 pandemic, the shift to virtual care became essential for the continued care of patients. Individuals with rheumatic and musculoskeletal diseases (RMDs) especially require frequent provider visits and close monitoring. To date, there have been limited studies examining inequities in health technology use among patients with RMDs. ObjectiveOur goal was to identify characteristics associated with patient portal use before and after the COVID-19 pandemic in a convenience sample of patients with RMDs from a large academic medical center. MethodsIn this cross-sectional study, Epic electronic medical record data were queried to identify established patients of the University of North Carolina Hospitals adult rheumatology clinic between November 1, 2017, through November 30, 2019. Demographic and clinical data were collected to compare MyChart (Epic's patient portal) users with nonusers before and after the COVID-19 pandemic. MyChart activation and use were modeled using logistic regression and adjusted odds ratios, and confidence intervals were estimated. ResultsWe identified 5075 established patients with RMDs who met the inclusion criteria. Prior to the pandemic, we found that younger age (P<.001), suburban residence (P=.05), commercial/state insurance (P<.001), military insurance (P=.05), and median income >US $50,000 (P<.001) were associated with significantly higher odds of MyChart activation. Male sex (P<.001), being of Black or African American (P<.001) or "other" race (P<.001), Spanish as a primary language (P<.001), rural residence (P=.007), Medicaid insurance (P<.001), and median income of <US $25,000 (P=.01) were associated with lower odds of MyChart activation. Following COVID-19, younger age (P<.001), commercial insurance (P=.03), state insurance (P=.02), and median income of US $50,000-75,000 (P=.01) were associated with significantly higher odds of MyChart use. However, being of Black or African American (P<.001) or "other" race (P=.01), Spanish as a primary language (P=.002), male sex (P=.004), rural residence (P=.005), and having no insurance (P<.001) or Medicaid (P=.008) were associated with lower odds of MyChart use. ConclusionsResidence in a rural area, being of minority race/ethnicity, older age, male sex, lower median income, Medicaid, being uninsured, and non-English primary language are associated with lower odds of patient portal activation and use. Future health policy and clinical practice measures should focus on reducing barriers to health technology adoption among these groups.